e-Transformation: Enabling New Development Strategies - Hanna, Nagy K. (Innovation, Technology, and Knowledge Management, 2010)
Could information and communication technology (ICT) become the transformative tool for a new style of global development? Could ICT promote knowledge-based, innovation-driven, and smart, adaptive, participatory development? As countries seek a way out of the present period of economic contraction, they are trying to weave ICT into their development strategies, in the same way organizations have learned to use ICT to transform their business models and strategies. This integration offers a new path to development that is responsive to the challenges of our times. In e-Transformation, Nagy Hanna identifies the key ingredients for the strategic integration of ICT into national development, with examples from around the world. He draws on his rich experience of over 35 years at the World Bank and other aid agencies to outline the strategic options involved in using ICT to maximize developmental impacttransforming public service institutions, networking businesses for innovation and competitiveness, and empowering communities for social inclusion and poverty reduction. He identifies the key interdependencies in e-transformation and offers a holistic framework to tap network effects and synergies across all elements of the process, including leadership, cyber policies, institutions, human resources, technological competencies, information infrastructure, and ICT uses for government, business, and society. Integrating analytical insights and practical applications across the fields of development, political economy, public administration, entrepreneurship, and technology management, the author candidly argues that e-transformation, like all bold ideas, faces implementation challenges. In particular, the aspiration-reality gap needs to be systematically addressed if ICT-enabled innovation and transformation is to become a development practice. E-transformation is first and foremost about thinking strategically and creatively about the options made possible by the information technology revolution in the context of globalization. To this end, the author provides tools and best practices designed to nurture innovation, select entry points, prioritize among competing demands, and sequence and scale up. He outlines the roles of all participantspolitical, managerial, entrepreneurial, social and technicalwhose leadership is essential for successful innovation.